A Case Report of Leptomeningeal Myelomatosis and Rapid Improvement with Regimen Consisting of Daratumumab, Pomalidomide, Vincristine, Procarbazine, and Dexamethasone - Jew Win Kuan; Sing Ling Chai; Pathmanathan Rajadurai; Lee Gong Lau; Joseph Uchang; Sharifah Noor Akmal Syed Husain (Case Reports in Hematology)
Central nervous system (CNS) involvement in multiple myeloma (MM) (MM-CNS) in the form of leptomeningeal myelomatosis or brain parenchyma plasmacytoma is rare, causing challenges in clinical diagnosis and treatment. We would like to report a case of leptomeningeal myelomatosis and illustrated the challeges. A 61-year-old man was diagnosed with MM with left paravertebral plasmacytoma, R-ISS II with high suspicion of double-hit MM, either biallelic aberrancy of TP53 or del(17p) and IGH aberrancy depending on the definition chosen, treated with lenalidomide-bortezomib-dexamethasone and local radiotherapy, later developed systemic relapse and progression to MM-CNS in the form of leptomeningeal myelomatosis. A modified CNS-based treatment not reported before, consisting of daratumumab, pomalidomide, vincristine, procarbazine, and dexamethasone, brought a rapid clinical improvement and warrants a further study. Incorporation of intrathecal thiotepa into the regimen would likely increase the efficacy.